Alcohol use among amateur sportsmen in Ireland - ALLWRIGHT, SHANE; O'FARRELL, ANNE (My University, 2010)
Background The objective of this study was to establish baseline data on alcohol consumption patterns, behaviours and harms among amateur sportsmen in the Republic of Ireland. Findings The study presents findings from the baseline survey for a cluster randomised controlled trial to evaluate the effectiveness of a community intervention programme to reduce problem alcohol use among a representative sample of Gaelic Athletic Association (GAA) clubs in two counties in the Republic of Ireland. Self reported alcohol use, prevalence of binge drinking, AUDIT scores and alcohol-related harms were assessed in amateur GAA sportsmen aged 16 years and over. Nine hundred and sixty (960) players completed questionnaires (72% response rate). Mean age was 24.0 years (S.D. 5.2). Of those aged 18 years or over, 75% had post-primary education; most (864, 90%) were current drinkers and 8.2% were regular smokers. The self-reported average yearly alcohol consumption was 12.5 litres. Almost one third (31%) of current drinkers reported drinking over the recommended limit of 21 standard drinks per week and just over half (54.3 %) reported drinking 6 or more standard drinks in a row at least once a week (regular binge drinking). Of those who (self) completed the Alcohol Use Disorder Identification Test (AUDIT) questionnaire, three-quarters (74.7%) had a score of 8 or more; 11.5% had a score of 20 or above warranting referral for diagnostic evaluation and treatment. Almost all (87.6%) of the 864 drinkers reported experiencing at least one harm due to their drinking. These alcohol misuse outcomes were higher than those found in a nationally representative sample of males of a similar age. There were strong associations between regular binge drinking and reporting harms such as being in a fight (adjusted odds ratio (OR) 2.02, p<0.001), missing time from work or college (adjusted OR 1.39, p=0.04) or being in an accident (adjusted OR 1.78, p=0.04). Conclusions These male amateur sportsmen reported high rates of alcohol consumption and alcohol-related harm.
PUBLISHED
Keywords: alcohol use; binge drinking; GAA; sportsmen